PERAN PEMBELAJARAN BERDIFERENSIASI DALAM PENGUATAN KARAKTER MENURUT TEORI BELAJAR HUMANISTIK TAHUN 2019-2024 - Pradipta, Anindhyta Putri; Ngabiyanto; Wadiyo; Bambang Subali; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Differentiated learning is one of the learning paradigms developed in the Merdeka Curriculum in response to the diversity of learners. Differentiated learning in the perspective of humanistic learning theory should be applied in elementary schools to overcome challenges in developing students' potential. The purpose of writing this article is to find out the research trends of differentiated learning for strengthening the character of students in elementary schools in 2019-2024. The writing of this article uses a literature study with the PRISMA (Preferred Items for Systematic Reviews and MetaAnalysis) technique. The results of the research on differentiated learning trends in character strengthening from the perspective of humanistic theory from 2019-2024 obtained several findings, namely the integration of humanistic learning theory in this learning has a positive impact on the development of students‘ individual potential and encourages the emergence of positive characters such as self-confidence, curiosity, and students’ ability to express themselves.